Effect of creatine pyruvate supplement, a novel compound, on lipid and protein metabolism in male rats - Kong, Yili; Su, Xiaoqian; Chen, Juan; Ma, Haitian; Zou, Sixiang (The Indian Journal of Animal Sciences, 2012)
The study was conducted to assess the effects of creatine pyruvate (Cr-Pyr) on lipid and protein metabolism in male rats. Healthy adult male Sprague-Dawley (SD) rats (40) were randomly assigned to control group (CG) and 3 experiment groups (EG) administrated with 750 (EG1), 1500 (EG2), or 3000 (EG3) mg/kg Cr-Pyr daily for 42 d. The fat mass in male rats of EGs was lower and relative muscle weight was significantly higher in EG2 and EG3 than CG. The content of serum HDL-C and hepatic TC was significantly lower in EG2, and male rats of EG3 had significantly lower hepatic TG as compared to those in CG. Supplementation of male rats with 3000 mg/kg Cr-Pyr significantly decreased the serum leptin concentration but increased insulin. Serum IGF-1 was thought statistically not significantly difference but its level elevated in EGs compared to CG. The expressions of HSL in fat and peroxisome proliferators-activated receptor a mRNA in liver were enhanced in EG2 and EG3 than CG. Supplementation of Cr-Pyr resulted in a significant increase in muscle protein content in EGs. Hepatic GPT was increased in EGs, but no effect on hepatic GOT activity. Supplementation of Cr-Pyr resulted in significant increase in muscle myogenin mRNA expression, while muscle mRNA abundance of myostatin (MSTN) was unaffected. The results described herein demonstrated that supplementation of Cr-Pyr was accompanied by significant elevated levels of lipolysis and increased muscle protein synthesis through the regulation of various metabolic parameters in male rats.